Chapter Assessing intimate partner violence in African countries through a model-based composite indicator - Parroco, Anna Maria (Proceedings e report, 2023)
Violence against women has been recognised to affect all dimensions of women's lives and health, involving both the physical and mental conditions of victims and their general well-being. Intimate partner violence (IPV) - characterized by one of the partners seeking power and control over the other - can be identified as either emotional, physical, or sexual abuse. Recent data show that 33% of ever-married women in Sub-Saharan Africa have survived this form of abuse. The literature lacks an overall measure of violence suitable for surveys since the Composite Abuse Scale (Revised) - Short Form captures IPV mostly in a clinical setting. The data here used are drawn from the Demographic and Health Survey (DHS). They are part of fifteen surveys that include a module on domestic violence and were carried out in African countries mostly from 2015 to 2018. All women selected for this sample are married women, aged 15-64. Three logistic regression models were previously defined to investigate the determinants of physical, emotional and sexual abuse - independently. In these models, the history of violence - defined as witnessing parental violence, rape by a man other than her partner, and number of abusers in life - turned out to be crucial in predicting violence itself. The intensity of how justified wife-beating is by women themselves and the number of control issues also resulted as significant across all models. On the other hand, the partner's high education and higher wealth turned out to be protective factors. On these bases, the definition and construction of a composite indicator of IPV with a Structural Equation Model (SEM) are already underway. The possibility of ranking the units of analysis according to the level of the IPV indicator can allow governmental and non-governmental organizations to implement socio-educational interventions that are better targeted to the actual needs of each context.